Bridging Divides: Islamic Communication in the Modern Era - Bhat, Ali Muhammad (Journal of Islamic Communication Studies, 2025)
Communication plays a significant role in modern-day life. It is the process of sharing ideas, information, and messages with others. It encompasses writing and speaking, as well as nonverbal communication (such as facial expressions, body language, or gestures), visual communication (including images, pictures, paintings, photography, video, or film). The major electronic communication (including telephone calls, email, cable television, or satellite broadcasts) and social media have impact on human mind. Such communication is a vital part of community and personal life and is also important in business, education, and any other situation where people encounter each other. An attempt is made to present the Islamic Model of Communication, which states that communication should be for the betterment of society and to encourage good deeds. Such a model is based on divine guidance, which is based on messengers who communicate or forward to the general public. Considering its divine origin, the insights were drawn from the Quran, Sunnah of the Prophet and renowned scholars and established communication theories to validate the argument.